Analisis Faktor Determinasi Penanaman Modal Asing (PMA) Di Provinsi Gorontalo - Nurtina, Sitti; Mahadi, Nur Rizky Putri (Universitas Dharma Andalas, 2025)
Abstract Referring to the data on the realization of foreign investment (FDI) in 2022, it shows that Gorontalo is in position 32, when compared to other provinces on the island of Sulawesi, Gorontalo Province is in 4th place out of a total of 6 provinces. This shows that there are determinant factors that affect foreign investment in Gorontalo Province. The method used in this research is descriptive qualitative. The research location is at the Investment and One-Stop Integrated Service Office of Gorontalo Province. Data collection techniques used observation, interview, and documentation. Data sources consist of primary data and secondary data. The data analysis technique consists of data reduction, data presentation and conclusion drawing. The results of this study show: 1) Infrastructure is inadequate. Infrastructure limitations in Gorontalo Province such as roads, ports, transportation, and other inadequate supporting facilities hinder foreign investment. 2) Complicated regulations and policies. The licensing process, especially business licensing, directly affects the desire and decision of prospective entrepreneurs or investors to invest. However, the licensing process is lengthy and complex, which often makes foreign investors hesitant to invest. 3) Human resources; limited skilled and trained human resources (HR) can be an obstacle for foreign companies wishing to operate and is an important challenge for foreign investment in Gorontalo. 4) Competition with other regions; Gorontalo when compared to other regions in Sulawesi is still in the second to last position so other regions that are more advanced or offer more attractive incentives can attract foreign investors. Abstrak Merujuk pada data realisasi investasi penanaman modal asing (PMA) tahun 2022 menampilkan yaitu Gorontalo berada di posisi 32, bila dibandingkan dengan Provinsi lain yang ada di pulau Sulawesi, Provinsi Gorontalo berada di urutan 4 dari total 6 Provinsi. Hal ini menunjukan bahwa ada faktor-faktor determinasi yang mempengaruhi penanaman modal asing di Provinsi Gorontalo. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Lokasi penelitian adalah di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Gorontalo. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Sumber data terdiri atas data primer dan data sekunder. Teknik analisis data yang dilakukan terdiri dari reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini menunjukkan: 1) Infrastruktur belum memadai. Keterbatasan infrastruktur di Provinsi Gorontalo seperti jalan, pelabuhan, transportasi, dan fasilitas pendukung lainnya yang belum memadai menghambat investasi asing. 2) Regulasi dan kebijakan yang rumit. Proses perizinan, khususnya perizinan usaha secara langsung berpengaruh terhadap keinginan dan keputusan calon pengusaha atau investor untuk menanamkan modalnya. Namun, proses perizinan memakan waktu yang panjang dan kompleks, sehingga sering kali membuat investor asing ragu untuk berinvestasi. 3) Sumber daya manusia; keterbatasan sumber daya manusia (SDM) yang terampil dan terlatih dapat menjadi kendala bagi perusahaan asing yang ingin beroperasi dan merupakan tantangan penting bagi penanaman modal asing di Gorontalo. 4) Persaingan dengan daerah lain; Gorontalo jika dibandingkan daerah lain di Sulawesi masih berada di posisi kedua dari terakhir menjadi daerah lain yang lebih maju atau menawarkan insentif lebih menarik bisa menarik perhatian investor asing.